The Use of Scapular Bone Flaps During Head-and-Neck Reconstruction: Functional, Orthopedic, and Quality of Life Analyses of Flap-Harvest-Related Deficits. Issue 7 (14th October 2022) - Valentini, Valentino; Di Giacomo, Giovanni; Di Giorgio, Danilo; Monaca, Marco Delia; Priore, Paolo; Piscitelli, Luigi; Battisti, Andrea
Abstract : Abstract: The authors sought correlations between harvesting of the scapular bone tip free flap used for head-and-neck reconstruction and any shoulder function deficit, particularly at the level of the rotator cuff. The flap permits reconstruction of large and diverse regions of the head and neck, but long-term harvest morbidity has not been investigated extensively. The authors analyzed the clinical records of all patients who underwent head-and-neck reconstructions using free scapular tip flaps in our department over the past 5 years. The inclusion criteria were complete clinical and radiological documentation and follow-up for at least 12 months. Two populations, a surgical and control population, were analyzed. All patients in both populations underwent the simple shoulder test, an internationally validated self-administered test that highlights functional shoulder deficits, and 3 additional tests at orthopedic visits: the external rotation test, Patte test, and external rotation lag sign test. A head-and-neck cancer-specific questionnaire (University of Washington Quality of Life, version 4) was completed by the surgical patients. All statistical analyses were performed using Software IBM SPSS Statistics (IBM Corp., Armonk, NY). A total of 19 patients met the inclusion criteria: 11 males (57.8%) and 8 females (42.2%) of mean age 60.9 years (range 23–75 years). In addition, 20 age-and sex-matched volunteers with no history of shoulder pathology were evaluated in terms of shoulder functionality. The average score on the simple shoulder test was 10.55 in the healthy population versus 8.31 in the study population ( P < 0.001); in particular, shoulder strength differed between the groups. Similarly, the orthopedic examinations revealed clinically significant differences between the controls and patients on the Patte test and external rotation lag sign test (both P < 0.001), but not the external rotation test ( P > 0.001). The mean University of Washington Quality of Life was 73.39; most patients reported good quality of life (52.6%), followed by very good (15.7%). The free scapular bone tip flap is valuable for reconstruction of head-and-neck defects; the long and reliable vascularpedicle allows rapid patient mobilization. Morbidity was confined to small reductions in shoulder strength and external rotation, which do not affect quality of life.